Characteristics of mid-infrared PAH emission from star-forming galaxies selected at 250 μm in the North Ecliptic Pole field. (11th December 2018) - Kim, Seong Jin; Jeong, Woong-Seob; Goto, Tomotsugu; Lee, Hyung Mok; Shim, Hyunjin; Pearson, Chris; Im, Myungshin; Matsuhara, Hideo; Seo, Hyunjong; Hashimoto, Tetsuya; Kim, Minjin; Chiang, Chia-Ying; et al.
Abstract: Evolutionary properties of infrared (IR) luminous galaxies are important keys to understand dust-obscured star formation history and galaxy evolution. Based on near- to mid-IR imaging with nine continuous filters of the AKARI space telescope, we present the characteristics of dusty star-forming (SF) galaxies showing polycyclic aromatic hydrocarbon (PAH) features observed by the North Ecliptic Pole (NEP) wide field survey of AKARI and Herschel. All the sample galaxies from the AKARI/NEP-Wide data are selected based both on the Herschel/SPIRE 250 μm detection and optical spectroscopic redshift data. The physical modeling of spectral energy distribution (SED) using all available data points from u * to sub-mm 500 μm band, including WISE and PACS data where available, takes unique advantages of the continuous near- to mid-IR coverage, the reliable constraint on the far-IR peak, and spectroscopically determined accurate redshifts, as well as the energy balance principle byMAGPHYS . This enables us to derive physically meaningful and accurate total infrared luminosity and 8 μm (or PAH) luminosity consistently. Our sample galaxies are in the redshift range$z$ < 1, and the majority of them appear to be normal SF/spiral populations showing PAH features near 8 μm. These SF galaxies showing PAHs in the mid-IR include various types, from quiescent to starbursts. Some of our sample show shortage of 8 μm luminosity compared to the total IR luminosity and this PAH deficit gets severe in more-luminous IR galaxies, suggesting PAH molecules in these galaxies are destroyed by a strong radiation field from the SF region or a large amount of cold dust in the interstellar medium. The specific SFR of our sample shows mass-dependent time evolution which is consistent with a downsizing evolutionary pattern.